An Examination of the the Simpsons' Adaptation of Hamlet - Batul Musavi; Laleh Atashi (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
This research traces the changes made to Shakespeare’s Hamlet by The Simpsons which is a medium different from literature. In one part of The Simpsons, a TV series with global popularity, a short adaptation of Hamlet is presented. In this article, this series is examined to understand how the medium uses Hamlet to criticize the American life style. This study investigates the transition of canonical literature to popular culture and adopts an interdisciplinary perspective to search the interactions of literature and media. First off, the generic conventions of The Simpsons and the history of its characters will be explained, and then the questions posed by Linda Hutcheon in adaptation studies will be addressed. This research indicates that the adaptation of Hamlet in The Simpsons, on the one hand parodies the highbrow culture and canonical literature, and on the other hand criticizes the stereotypes of the American nuclear family through exaggerated humor. Cultural critics in the United States have critiqued The Simpsons' ideological content but in Iran, animations have rarely received critical attention. This article will investigate how The Simpsons have responded to high culture through double adaptation.